Sincronismo e Interatividade com a Segunda Tela frente à Implementação da TV 3.0 no Brasil - Celestino, Antonio; Pernisa Júnior, Carlos (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia); 2024: Anais Estendidos do XXX Simpósio Brasileiro de Sistemas Multimídia e WebDO - 10.5753/webmedia_estendido.2024.243863, 2024)
This article aims to discuss the challenges of synchronization and interactivity for Digital TV 3.0 in Brazil. The standard being developed for the transmission of the TV 3.0 signal will bring combined broadcasting and broadband, in order to expand interactivity resources for the viewer. As the available interactive resources increase, questions arise about how these extra materials can be consumed and how a second screen can help in the interaction with such content, in synchronization with the main stream of a television program. Transmitting this content on the TV signal itself, instead of releasing it on the Internet, is a viable practice, but it will require production, transmission and synchronization efforts.